Extensive subcutaneous metastases from squamous cell carcinoma of the cervix in patient with HIV. Issue 1 (1st January 2001) - Amit, A.; Edwards, C. L.; Athey, P.; Kaplan, A. L.
Abstract : Advanced human immunodeficiency viral disease is associated with a high prevalence of cervical squamous intraepithelial and invasive lesions and probably with a rapidly progressive course of disease. Metastases to the skin occur rarely in cervical cancer, even in terminal stage of the disease. A patient with human immunodeficiency virus (HIV) for 14 years was diagnosed with squamous cell cancer of the cervix, Stage I-B2 in June 1997. She underwent successful radiotherapy. She then presented in January 1999 with recurrence evidenced by extensive subcutaneous nodules and multiple metastases. The patient developed rapidly progressive disease and died within two months. Patients with HIV and cervical cancer may present with a more aggressive course of disease. Aggressive treatment and closer follow-up may be indicated.